Cases on transnational learning and technologically enabled environments - Mukerji, Siran; Tripathi, Purnendu, 1975-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
Whether by synergy or by synthesis, development and technology are becoming synonymous in every domain. This book reports on national and international initiatives undertaken to adapt advancements in information and communication technology and successfully face the challenges posed by various social and economic forces. The international research in this book represents instances of institutions that are in transition as well as those that are readily using technology in education.
Web-Based Instructions / Mohammed Saleh Al Balawi -- Blended Assessment Methods in Online Educational Programs in Turkey / Erman Yukselturk, Orhan Curaoglu -- Generic Themes for Developing Research Skills through E-Learning / Abbas Bazargan, Amin Mousavi -- Effectiveness of Interactivity for Enhanced Undergraduate Learning / Chris Evans, Luis Palacios -- The Challenges of Technology-Enhanced Instructional System in Nigeria / O. A. Sofowora ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on August 18, 2010).
Keywords: Transnational education; Educational technology; Internet in education; Synchronous online classrooms; Personalized t-learning; Desktop virtual environments; Collaborative knowledge construction; E-learning in higher education; Virtual teacher training; Foreign language learning; Competence based education; Blended assessment methods; Enhanced undergraduate learning; Electronic books